Kinerja Pegawai: Lingkungan Kerja, Etos Kerja, dan Disiplin Kerja Melalui Kepuasan Kerja pada Biro Administrasi Pimpinan - Roni Putra Harefa; Elfiswandi Elfiswandi; Jhon Veri (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This study aims to see the influence of work environment, work ethic and work discipline on employee performance through job satisfaction as an intervention in the Administrative Bureau of the West Sumatra Provincial Secretariat. The type of research used is quantitative. The population in this study is all employees of the Administrative Bureau of the West Sumatra Provincial Secretariat which totals 50 employees. The sample selection technique uses total sampling and obtained 50 samples. The analysis method uses Structural Equition Modeling (SEM) Analysis with Partial Least Square (PLS). Based on the results of the analysis, it can be concluded that the work environment has a positive and significant effect on job satisfaction. Work ethic has a positive and significant effect on job satisfaction. Work discipline has no effect on job satisfaction. The work environment has a positive and significant effect on employee performance. Work ethic does not have a significant effect on employee performance. Work discipline does not have a significant effect on employee performance. Job satisfaction has a positive and significant effect on employee performance. The work environment has a positive and significant effect on employee performance through job satisfaction. Work ethic has a significant effect on employee performance through job satisfaction. Work discipline does not have a significant effect on employee performance through job satisfaction at the West Sumatra Province Secretariat Leadership Administration Bureau